Lessons From China For Africa - Dollar, David, 1954- 1954- (The World Bank, 2008)
China has been the most successful developing country in this modern era of globalization. Since initiating economic reform after 1978, its economy has expanded at a steady rate over 8 percent per capita, fueling historically unprecedented poverty reduction (the poverty rate declined from over 60 percent to 7 percent in 2007). Other developing countries struggling to grow and reduce poverty are naturally interested in what has been the source of this impressive growth and what, if any, lessons they can take from China. This paper focuses on four features of modern China that have changed significantly between the pre-reform period and today. The Chinese themselves call their reform program Gai Ge Kai Feng, "change the system, open the door." "Change the system" means altering incentives and ownership, that is, shifting the economy from near total state ownership to one in which private enterprise is dominant. "Open the door" means exactly what it says, liberalizing trade and direct investment. A third lesson is the development of high-quality infrastructure: China's good roads, reliable power, world-class ports, and excellent cell phone coverage throughout the country are apparent to any visitor. What is less well known is that most of this infrastructure has been developed through a policy of "cost recovery" that prices infrastructure services at levels sufficient to finance the capital cost as well as operations and maintenance. A fourth important lesson is China's careful attention to agriculture and rural development, complemented by rural-urban migration